2020
DOI: 10.1108/ijchm-10-2019-0904
|View full text |Cite
|
Sign up to set email alerts
|

Robot with humanoid hands cooks food better?

Abstract: Purpose Robotic chefs are starting to replace human chefs in restaurant industry. Whether customers have a good food quality prediction may have an important effect on their patronage decision. Based on the stereotype content model, the purpose of this paper is to investigate the impact of robotic chef anthropomorphism on food quality prediction through warmth and competence. Design/methodology/approach An empirical analysis was done to test the theoretical model by using the SmartPLS software. A nonhuman-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(77 citation statements)
references
References 61 publications
2
71
0
4
Order By: Relevance
“…A robot's human‐likeness could be modified differently depending on the context. For instance, a recent study focused on chef robots found that customers' perception of food quality was more positive when cooked by a robot with human‐like hands compared to mechanic hands (Zhu & Chang, 2020). In this regard, the current study focuses on restaurants as a prototypical context in the hospitality sector that involves interactions between customers and frontline agents combining functional and social skills.…”
Section: Discussionmentioning
confidence: 99%
“…A robot's human‐likeness could be modified differently depending on the context. For instance, a recent study focused on chef robots found that customers' perception of food quality was more positive when cooked by a robot with human‐like hands compared to mechanic hands (Zhu & Chang, 2020). In this regard, the current study focuses on restaurants as a prototypical context in the hospitality sector that involves interactions between customers and frontline agents combining functional and social skills.…”
Section: Discussionmentioning
confidence: 99%
“…The career uncertainty and job insecurity make them feel emotionally exhausted (Ito and Brotheridge, 2001). The using of AI may replace employees' position in their organization (Zhu and Chang, 2020), and affect employees' career development. Employees' personal needs may not be satisfied through careers; they are likely to suffer career dissatisfaction (Karatepe, 2012).…”
Section: Artificial Intelligence Awareness and Job Burnoutmentioning
confidence: 99%
“…Empirical studies are largely devoted to the demand-side perspective of the use of service robots in tourism with an emphasis on customer attitudes towards and acceptance of robots (Ivanov, Webster & Garenko, 2018;Ivanov, Webster & Seyyedi, 2018;Lin, Chi & Gursoy, 2019;Lu, Cai & Gursoy, 2019;Stock & Merkle, 2017;, customers' trust in robots (Park, 2020;Tussyadiah, Zach & Wang, 2020), tasks perceived by tourists as appropriate for robotisation (Ivanov & Webster, 2019a, 2019b, customer evaluation of service robots (Tussyadiah & Park, 2018), the impact of language styles in the service encounter (Choi, Liu & Mattila, 2019), the effects of robotic service on guest evaluations of hotel brand experience (Chan & Tung, 2019). Studies have also investigated the role of robots in the service recovery process (Ho, Tojib & Tsarenko, 2020), the nudging effect of robots on stimulating proenvironmental behaviour of tourists (Tussyadiah & Miller, 2019), heart-warming interaction between customers and robots (Nakanishi et al, 2020), the effect of service robot attributes on customers' expected rapport building with robots (Qiu et al, 2020), tourists' perceptions about the appearance of robots (Yu, 2018(Yu, , 2020Yu & Ngan, 2019), the impact of robot service on purchase intentions (Zhong et al, 2020) and robot use intentions (de Kervenoael et al, 2020), the impact of robotic chef anthropomorphism on food quality prediction (Zhu et al, 2020). The research focus on tourists is logical because if customers do not want to be served by robots, if they resist, avoid, or do not wish to pay for robot-delivered services, then tourism and hospitality companies would find it challenging to introduce robots in their operations.…”
Section: Rationalementioning
confidence: 99%